Pengembangan Ekonomi Lokal Produk Unggulan Tape Singkong dan Turunannya Melalui Inovasi Teknologi di Kecamatan Medan Tuntungan - Masril, Julfikri (Universitas Islam Sumatera Utara, 2024)
Cassava tape is one of the superior local products which has great potential to be developed in Medan Tuntungan District. This research aims to explore strategies for developing cassava tape and its derivatives through technological innovation. The research method used is a qualitative and quantitative approach with data collection techniques in the form of interviews, surveys and field observations. Analysis shows that technological innovation, product diversification and marketing digitalization are the keys to success in increasing product added value. Implementation of this strategy is expected to encourage local economic growth and improve community welfare.